SELECTION OF INDUSTRY CLUSTER DEVELOPMENT STRATEGY AND KNOWLEDGE MANAGEMENT STRATEGY AT LATEX DIPPED GOODS INDUSTRIAL CLUSTER - Dedi Sugiarto, M Syamsul Ma'arif Illah Sailah, Sukardi dan Suharto Honggokusumo (Jurnal Teknologi Industri Pertanian, 2010)
ABSTRACT  One of the problems encountered in developing industrial cluster is how to manage the collaboration especially knowledge sharing among cluster members (industry, governments and supporting institution). On the other side, knowledge management activities in cluster should be tightly related to objectives and strategy of the cluster itself. This article presents a model for selecting industrial cluster development strategy and selecting knowledge management strategy by taking a case study at  small and medium enterprises (SME) latex dipped goods cluster in West Java and Banten provinces. Fuzzy analytical hierarchy process was used in this research. The results shows that innovation and technology strategic initiative was the most important initiative for developing latex dipped cluster where  supporting institutions acts as main actor. Combination of codification and personalization strategy was the most important knowledge management strategy to support innovation and technology strategic initiative.  Keywords: industry cluster, strategy,  knowledge  management, fuzzy analytical hierarchy process,  latex dipped goods